Effect of doctor–patient news-induced moral judgments on pain empathy for doctors and patients in China - Li, HuiLing; Zhao, Dong; Yang, BinJie; Zhao, YuHui; Huang, HanZhi; Jiang, Huan; Chen, MeiFen; Zhou, Qiang; Ying, Liang (Frontiers in Neuroscience, 2022)
Objective Pain empathy’s preferential nature tends to trigger prejudice and intergroup conflicts. Given the current degree of proliferation of doctor–patient conflict news in China, this study aims to determine whether readers of doctor–patient news-initiated moral judgments prefer pain empathy for doctors or patients. Materials and methods This study utilized localized doctor–patient news with high or low moral performance (based on morality ratings of patients’ behaviors) as moral-judgment-eliciting materials, and painful pictures as pain empathy-eliciting materials. The event-related potential (ERP) technique was utilized to assess moral judgment’s effect on the cognitive empathy component and to investigate electroencephalogram signals’ accuracy in classifying four brain response patterns when facing doctor or patient is experiencing or not experiencing pain. Results Under low moral text material, participants exhibited smaller mean wave amplitude of positive 300 (P3) and late positive potential (LPP) to painful pictures than non-painful pictures when facing patients; under high moral text material, participants exhibited larger mean wave amplitude of P3 and LPP to painful pictures than non-painful pictures when facing doctors. Electroencephalogram (EEG) signals’ classification accuracy was significant in 0–1,000 ms in both high and low moral judgments, but the classification accuracy was higher in low moral judgments in some cognitive empathy stages (0.51, 0.53–0.55, 0.66–0.79, and 0.88–1 s). Conclusion Under low moral judgment, individuals pay less attention to the patient’s (perpetrator’s) pain; under high moral judgment, individuals empathize with the doctor (the person praised), showing that news-induced moral judgment can sway readers’ empathy for different social groups. In cognitive empathy, individuals’ brain representations are more discriminatory under low than high moral judgments when confronted with pain by doctors and patients, which provides insight into objectively recognizing group bias.